2020
DOI: 10.3390/su12114798
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Organic Fraction of Municipal Solid Waste: Systematic Literature Review and Bibliometric Analysis of Research Trends

Abstract: The organic fraction is usually the predominant fraction in municipal solid waste, so its recycling is a potential alternative to disposal in landfill sites, as well as helping to reach targets included in the European Circular Economy Package. The existing body of knowledge in this research field is very large, so a comprehensive review of the existing scientific literature has been considered of interest to provide researchers and professionals with a detailed understanding of the status quo and predict the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Centrality is the degree of interaction of a research topic with other research topics. The density gives an idea of the level of development of that topic, measuring the internal cohesion of all the links between the keywords that describe the topic [43,44]. The diagrams are divided into four quadrants that capture the following four types of research topics:…”
Section: Detection Research Themes and Creation Of Two-dimensional Strategic Diagramsmentioning
confidence: 99%
“…Centrality is the degree of interaction of a research topic with other research topics. The density gives an idea of the level of development of that topic, measuring the internal cohesion of all the links between the keywords that describe the topic [43,44]. The diagrams are divided into four quadrants that capture the following four types of research topics:…”
Section: Detection Research Themes and Creation Of Two-dimensional Strategic Diagramsmentioning
confidence: 99%
“…e issues faced by current waste management systems are improper scheduling; that is, the waste collectors do not know that they had to pick the waste. ey also do not know precisely about the drop-off location [6]. One significant application is that IoT innovation has become an effective apparatus to manufacture brilliant urban communities.…”
Section: Introductionmentioning
confidence: 99%
“…With this process, in addition to identifying the relevant publications of the areas of study, their formal characteristics were identified. Below in Figure 1, a diagram of the procedure carried out is shown, using the methodological structure of Fernández-González et al [44] as a reference:…”
Section: Methodsmentioning
confidence: 99%